Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-31992-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering functional smooth muscle with spontaneous rhythmic contraction in vitro

Abstract: Oriented smooth muscle layers in the intestine contract rhythmically due to the action of interstitial cells of Cajal (ICC) that serve as pacemakers of the intestine. Disruption of ICC networks has been reported in various intestinal motility disorders, which limit the quality and expectancy of life. A significant challenge in intestinal smooth muscle engineering is the rapid loss of function in cultured ICC and smooth muscle cells (SMC). Here we demonstrate a novel approach to maintain the function of both IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…When primary cultured mouse ‘intestinal muscularis complexes’ (containing Kit + cells) were combined with electrospun poly-caprolactone scaffold sheets in vitro, spontaneous contractions were observed [ 65 ]. Similar findings occurred when electrospun poly-caprolactone scaffold sheets were seeded with STO feeder cells and primary MACS-purified mouse Kit + ICC [ 66 ], thus demonstrating attachment and alignment onto the scaffold sheets in vitro. In addition, when a primary mouse intestinal smooth muscle cell mixture was cultured on STO-seeded electrospun poly-caprolactone scaffold sheets, rhythmic contractions developed, and Kit + Ano1 + cells were observed after 10 weeks.…”
Section: Icc and Gi Therapysupporting
confidence: 58%
See 1 more Smart Citation
“…When primary cultured mouse ‘intestinal muscularis complexes’ (containing Kit + cells) were combined with electrospun poly-caprolactone scaffold sheets in vitro, spontaneous contractions were observed [ 65 ]. Similar findings occurred when electrospun poly-caprolactone scaffold sheets were seeded with STO feeder cells and primary MACS-purified mouse Kit + ICC [ 66 ], thus demonstrating attachment and alignment onto the scaffold sheets in vitro. In addition, when a primary mouse intestinal smooth muscle cell mixture was cultured on STO-seeded electrospun poly-caprolactone scaffold sheets, rhythmic contractions developed, and Kit + Ano1 + cells were observed after 10 weeks.…”
Section: Icc and Gi Therapysupporting
confidence: 58%
“…This included spontaneous contractions and the presence of gut cell types including Kit + cells. To further maintain the functionality of ICC in vitro, STO (SIM, Sandos Inbred Mouse) embryonic fibroblast feeder cells have been co-cultured with enriched murine Kit + ICC (purified from primary mouse intestinal smooth muscle cell mixture through the use of magnetic-activated cell sorting and an anti-Kit antibody) [ 66 ]. Intriguingly, this model maintained contractility and contained Kit + Ano1 + cells for up to 14 days.…”
Section: Potential Sources Of Iccmentioning
confidence: 99%
“…In addition to the soft lithographic strategy, the electrospinning fabrication technique has been widely utilized to manufacture random or highly aligned nano-/micro-fibrous membranes in dental tissue engineering applications such as periodontal regeneration [50,51,52] or pulp regeneration [53,54,55]. In particular, the electrospun 2D membranes with unidirectional alignments or controllable-aligned patterns of nano-fibers were investigated for specific cell orientations and migrations to regulate cellular responses to designed microenvironments [56,57]. However, there is the limitation to create 3D directional internal architectures to regulate cell or tissue orientations with structural similarities to PDLs because periodontal connective tissues have the spatially perpendicular or oblique angulations to tooth-root surfaces as described above [51,58].…”
Section: Pdl Regenerations With Angular Organization Using Topogramentioning
confidence: 99%
“…There is a shortage of literature demonstrating contraction of tissue-engineered grafts in vitro, including the lack of a reference protocol. Kobayashi et al determined that intestinal SMS seeded electrospun poly(3-caprolactone) scaffolds exhibited rhythmic contractions resulting in biomaterial contraction 42 . Krueger et al reported the ability of muscle cells, forming myotubes seeded on graphene foam to mediate consolidated micromovements 43 .…”
Section: Discussionmentioning
confidence: 99%